A STATEMENT OF DIFFERENTIAL CALCULUS IN CONTEXT OF CODOMAIN OF THE FUNCTION - Malešević, Jovan V. (Matematichki Bilten, 2012)
In this article we give an analogue of Statement 3 from [1] with appropriate geometrical interpretation in sense of codomain (image) of the function \(f(x)\).